2018
DOI: 10.2147/rmhp.s172860
|View full text |Cite
|
Sign up to set email alerts
|

Perceived threat and benefit toward community compliance of filariasis’ mass drug administration in Pekalongan district, Indonesia

Abstract: PurposeLymphatic filariasis (LF) is a chronic infection of Brugia malayi, Brugia timori, and Wuchereria bancrofti and is a mosquito-transmitted disease. Mass drug administration (MDA) needs to be done annually to control LF and requires adherence of endemic populations to take medication properly. Maintaining high coverage of MDA is a challenge because the activity needs to be done in several years. This study would like to know the compliance of the community in taking medication during MDA periods in Pekalon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
3
7
0
5
Order By: Relevance
“…The insignificant result in this study is in line with a study in Ethiopia (p=0.061). A similar result was obtained from research in Pekalongan which stated that perceived vulnerability, which is a component of perceived threats, did not affect treatment adherence (p=0.272) [27,29].…”
Section: Discussionsupporting
confidence: 81%
“…The insignificant result in this study is in line with a study in Ethiopia (p=0.061). A similar result was obtained from research in Pekalongan which stated that perceived vulnerability, which is a component of perceived threats, did not affect treatment adherence (p=0.272) [27,29].…”
Section: Discussionsupporting
confidence: 81%
“…The study in India found out that the subjects who did not consume the medication feared experiencing side effects and they "don't have faith in a tablet". 14 Perceived vulnerability, perceived severity, perceived benefits, and perceived barriers were determinants of adherence to the MDA program based on a study conducted by Widjanarko, et al 15 In general, the majority of respondents had a good perception and most of them felt the need to take preventive medicine for filariasis. 15 Several MDAs in various countries have encountered the mistrust of the communities in the MDA program.…”
Section: Discussionmentioning
confidence: 99%
“…14 Perceived vulnerability, perceived severity, perceived benefits, and perceived barriers were determinants of adherence to the MDA program based on a study conducted by Widjanarko, et al 15 In general, the majority of respondents had a good perception and most of them felt the need to take preventive medicine for filariasis. 15 Several MDAs in various countries have encountered the mistrust of the communities in the MDA program. These include suspicions that the drugs are being used to poison children, being used as birth control, and even cause erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…10 Beberapa wilayah juga melaporkan bahwa masih ditemukan positif antigenaemia pada siswa pada saat evaluasi TAS, baik yang nilainya di bawah cut of point (lulus TAS) maupun yang melebihi cut of point (gagal), di Kabupaten Agam Sumatera Barat TAS-1 (B. malayi), 11 dan di negara lain seperti Bangladesh ditemukan positif pada wilayah endemis tinggi (W. bancrofti). 12 Faktor yang mempengaruhi terjadinya penularan kembali LF (re-transmission) pada wilayah yang telah menyelesaikan POPM diantaranya adalah cakupan POPM yang rendah, 13,14,15,16 penolakan masyarakat karena reaksi efek obat, 17 metode surveilans, lingkungan (agen, vektor, dan reservoar), 18,19,20 faktor sosial demografi, serta perilaku masyarakat (perilaku berisiko dan kepatuhan minum obat). 20,21,22 Burgert-Bucker et al melaporkan bahwa terdapat hubungan yang potensial antara kegagalan pengobatan LF dengan kepadatan penduduk, pengobatan dengan Diethylcarbamazine Citrate (DEC)-Albendazole, POPM 6 tahun atau lebih, terkait pula dengan faktor lingkungan yaitu geografis, curah hujan lebih tinggi, serta indeks vegetasi yang tinggi.…”
Section: Pendahuluanunclassified
“…Hal ini serupa dengan penelitian/kajian sebelumnya yaitu sampel perempuan lebih mendominasi. 13,14 Karakteristik responden positif didominasi jenis kelamin laki-laki pada kelompok usia produktif yaitu kelompok usia (13-50 tahun). Kelompok usia produktif berjenis kelamin laki-laki mempunyai risiko lebih besar, diantaranya karena mobilitas yang tinggi serta lebih sering keluar rumah (bekerja diluar rumah).…”
Section: Hasilunclassified